Analysis of the Nature of the Fulfillment of the Obligation in Iran and in France Civil Codes - Zahra Babajani; Saeid Kheradmandy; Mohamad Javad Jafari (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractCompletion of ambiguity and the provision of accurate legal interpretations requires the examination of various legal opinions. Legal rights regarding ambiguity are contained in Article 265 of the Iranian Civil Code which states that if someone gives property to someone else, it is assumed that he has not done it without consideration. This has been a matter of years of debate between lawyers. Some of them considered the problem as proof that someone who gave property was compulsory, and they believed that the request for expropriation of property must prove that there was no obligation to give and deserve to receive repayment of the property. Others believe in the lack of certainty of the obligations of the giver and require proof of the right to accept the recipient of the property. The findings of this study indicate that what caused the disagreement in the court was due to the Brief Article of the Civil Code of Iran, and a lack of attention to the legislator's ultimate goals in the public interest, and a lack of understanding of the difference between